2019
DOI: 10.1101/561134
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intra-mitochondrial proteostasis is directly coupled to alpha-synuclein and Amyloid β 1-42 pathology

Abstract: Mitochondria have long been implicated in Parkinson’s disease (PD), however, it is not clear how mitochondrial impairment and alpha-synuclein pathology are coupled. We report here that intra-mitochondrial protein homeostasis plays a major role in alpha-synuclein fibril elongation, as interference with intra-mitochondrial proteases and mitochondrial protein import significantly aggravate alpha-synuclein aggregation. In contrast, direct inhibition of mitochondrial complex I, increase in intracellular calcium con… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…7,8 It interferes the proton gradient across the electron transport chain (ETC), thereby disrupting adenosine triphosphate (ATP) synthesis. A recent study by Lautenschläger et al 9 has found that the addition of FCCP leads to greater intracellular Aβ42 aggregation in a HEK293T cell model. As mitochondria are the power source of the cell, it is unsurprising that oxidative stress incurred in the presence of Aβ42 aggregation could lead to changes in its metabolism, and hence to the overall energetics of the cell.…”
Section: Introductionmentioning
confidence: 98%
“…7,8 It interferes the proton gradient across the electron transport chain (ETC), thereby disrupting adenosine triphosphate (ATP) synthesis. A recent study by Lautenschläger et al 9 has found that the addition of FCCP leads to greater intracellular Aβ42 aggregation in a HEK293T cell model. As mitochondria are the power source of the cell, it is unsurprising that oxidative stress incurred in the presence of Aβ42 aggregation could lead to changes in its metabolism, and hence to the overall energetics of the cell.…”
Section: Introductionmentioning
confidence: 98%